Negotiating development : rationales and practice for development obligations and planning gain - Healey, Patsy; Purdue, Michael; Ennis, Frank (London : E & FN Spon, 1995)
Planning gain is the legal process by which property development is linked to social provisions. This book examines the rationale for planning gain and development obligations and reviews the practice of development negotiation through a wide range of case histories.
pt. 1. The issues -- pt. 2. The practice -- pt. 3. Implications.
Includes bibliographical references (pages 261-270) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Land use -- Great Britain -- Planning; Planning -- Great Britain; City planning and redevelopment law -- Great Britain; Utilisation du sol -- Grande-Bretagne -- Planification; Planification -- Grande-Bretagne.; NATURE -- Natural Resources; BUSINESS & ECONOMICS -- Environmental Economics; BUSINESS & ECONOMICS -- Green Business; City planning and redevelopment law; Land use -- Planning; Planning; Great Britain